Geriatrician-led evidence-based Falls Prevention Clinic: a prospective 12-month feasibility and acceptability cohort study among older adults. Issue 12 (4th December 2018) - Davis, Jennifer C; Dian, Larry; Parmar, Naaz; Madden, Kenneth; Khan, Karim M; Chan, Wency; Cheung, Winnie; Rogers, Jessica; Liu-Ambrose, Teresa
Abstract : Objective: We assessed the feasibility and acceptability of delivering a geriatrician-led evidence-based Falls Prevention Clinic to older adults with a history of falls. Design: 12-month prospective cohort study. Setting: Vancouver Falls Prevention Clinic, Vancouver, British Columbia, Canada (www.fallsclinic.ca ). Participants: 188 community-dwelling older adults aged ≥70 years who received a baseline assessment at the Vancouver Falls Prevention Clinic due to having had at least one fall resulting in medical attention in the previous 12 months. Fifty-six per cent of participants were also participating in a randomised controlled trial. Measurements: Feasibility was ascertained by measuring demand (clinic attendance). Acceptability was measured by compliance with recommendations, completion of monthly fall calendars and patient experience. Results: The attendance was 65% of those eligible and invited. This indicates feasibility for demand. 155 received at least one of the following clinical management recommendations from four domains (compliance reported in %): (1) medication changes (78%); (2) exercise prescription (58%); (3) referrals to other healthcare professionals (78%); and/or (4) lifestyle modifications (35%) excluding exercise. Overall compliance to all recommendations was 69%. Patient experience was related to factors impacting patient perceived physical benefit and attributes influencing patient satisfaction. Conclusion: This study demonstrated the feasibility and acceptability of a multifactorial intervention approach based on best available evidence-based medicine.